Integrating Intelligent Process Automation With Human Resource Management for Enhancing Efficiency and Strategic Decision-Making - Vimala, Govindaraju; Sathis Kumar, Ganesan; Kalyani, Velusamy (IGI Global's, 2024)
The integration of intelligent process automation (IPA) into diverse corporate processes has brought about a revolution in productivity and efficiency across industries as it continues to evolve. The vital role that human resources management (HRM) plays in utilizing IPA to optimize organizational advantages is examined in this research. It talks about how HRM may help with IPA implementation by emphasizing personnel planning, change management, and strategic alignment. The chapter emphasizes how important it is for HRM to deal with the issues brought on by IPA, including employee resistance, skills gaps, and workforce relocation. HRM can guarantee that workers continue to play a crucial role in the increasingly automated workplace by promoting a culture of continual learning and adaptability. This chapter also emphasizes the mutually beneficial interaction between HRM and IPA, stressing that the smooth cooperation of automated processes and human talent will be essential to the nature of work in the future.